Preparing the Next Generation in Tanzania : Challenges and Opportunities in Education - Joshi, Arun R.; Gaddis, Isis (Washington, DC: World Bank, 2015)
Human capital refers to a broad range of knowledge, skills, and capabilities that are needed for life and work and that are typically build through quality education. Countries that fail to invest consistently in education often do not experience robust economic growth because investments in physical infrastructure, such as dams, roads, and airports as well as developments in other economic sectors such as banking or information technology, are often constrained and yield low returns in the absence of an adequately educated work force.